A framework for enabling metaverse for sustainable manufacturing - Assad, Fadi; Konstantinov, Sergey; Patsavellas, John; Salonitis, Konstantinos (Elsevier, 2024)
Newly introduced technologies often require time for adoption and integration into manufacturing environments, for several reasons including technological maturity, adoption costs, and skills gaps. The inclusion of sustainability as a new requirement for both customers and producers adds further complexity to the equation. As metaverse technology became available, it became logical to establish a set of requirements to harness its new potential and create a sustainability-oriented framework for seamless integration into modern smart manufacturing environments. Against this background, the current work introduces a framework aimed at harnessing the potential of the metaverse to enhance manufacturing sustainability. As a case study, an industrial workshop was analysed and evaluated using the proposed framework. The findings help create a future plan for leveraging the use of the metaverse and prioritising its requirements.
Keywords: 4014 Manufacturing engineering; Metaverse; Sustainable Manufacturing; Sustainability; Technology Adoption